2019
DOI: 10.26452/ijrps.v10i2.720
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical study in ethanolic leaves extract of Aloe vera using Gas chromatography

Abstract: Medicinal plant Aloe vera are reported to have anti-cancer properties. In the present work, a phytochemical study in Aloe vera was evaluated qualitatively and further analysed using gas chromatography. Aloe vera leaves were washed, shade dried and homogenized to get a filtrate which was extracted in ethanol using Soxhlet apparatus. The ethanolic extract was subjected to various phytochemical tests and also evaluated using gas chromatography. As a result, the qualitative phytochemical analysis of A.vera ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Darshan (2017) reported that Aloe vera contains saponin, alkaloids and flavonoids in methanol extraction. These types of phytochemicals are involved in plant defence mechanisms against various microorganisms with steroids involved in antibacterial properties, flavonoids with anti-oxidant function and tannins are known to be involved in the anti-cancer action (Jannathul et al, 2019). All the phenolic compounds are involved in scavenging free radicals with their reducing properties.…”
Section: Phytochemical Screening Of Aloe Vera Gelmentioning
confidence: 99%
See 1 more Smart Citation
“…Darshan (2017) reported that Aloe vera contains saponin, alkaloids and flavonoids in methanol extraction. These types of phytochemicals are involved in plant defence mechanisms against various microorganisms with steroids involved in antibacterial properties, flavonoids with anti-oxidant function and tannins are known to be involved in the anti-cancer action (Jannathul et al, 2019). All the phenolic compounds are involved in scavenging free radicals with their reducing properties.…”
Section: Phytochemical Screening Of Aloe Vera Gelmentioning
confidence: 99%
“…All the phenolic compounds are involved in scavenging free radicals with their reducing properties. All these compounds are of pharmaceutical importance as they possess properties such as anti-cancer, anti-diabetic, analgesic, antibacterial and antifungal activity (Jannathul et al, 2019).…”
Section: Phytochemical Screening Of Aloe Vera Gelmentioning
confidence: 99%